2015
DOI: 10.1159/000434684
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Tuberculosis Risk in Patients Receiving Anti-Tumor Necrosis Factor-α Treatment

Abstract: Background: Tumor necrosis factor (TNF)-α inhibitors are known to increase the risk of tuberculosis (TB). Objectives: To examine the factors associated with an increased risk of TB in patients receiving anti-TNF-α treatment (aTNF-α-T). Method: Of 3,094 patients who received aTNF-α-T between 2003 and 2013, a total of 1,964 subjects with a follow-up time longer than 6 months were identified and included in this retrospective analysis. Potential risk factors for the development of TB in patients receiving aTNF-α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
4
28
1
3
Order By: Relevance
“…In our study, men were more likely to develop TB in anti‐TNF‐α‐naïve group whereas a non‐significant tendency of having TB was observed in male anti‐TNF‐α users, implying no confounding effect of being male on anti‐TNF‐α therapy‐related TB risk. In fact, previous studies from Turkey reported no effect of gender in RD patients under anti‐TNF‐α therapy . On the other hand, analysis of the RR in gender subgroups showed significantly elevated risk only in men.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In our study, men were more likely to develop TB in anti‐TNF‐α‐naïve group whereas a non‐significant tendency of having TB was observed in male anti‐TNF‐α users, implying no confounding effect of being male on anti‐TNF‐α therapy‐related TB risk. In fact, previous studies from Turkey reported no effect of gender in RD patients under anti‐TNF‐α therapy . On the other hand, analysis of the RR in gender subgroups showed significantly elevated risk only in men.…”
Section: Resultsmentioning
confidence: 78%
“…In addition, we were not able to collect data regarding isoniazid use as the drug is distributed from tuberculosis control dispensaries which do not submit their electronic prescriptions to PIS. Although this might have influenced the observed risk of TB, a recent study in Turkey reported no association between isoniazid chemoprophylaxis and TB . We also did not assess continuity of anti‐TNF‐α therapy or its doses, or concomitant corticosteroid dosages among anti‐TNF‐α users, which could differentially create a background risk for TB.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In this issue of Respiration , Borekci et al [6 ]report their retrospective analysis of patients who were treated with a TNF-α blocker and followed up for at least 6 months during 2003-2013 at a single centre in Turkey. The most common underlying autoimmune inflammatory conditions were ankylosing spondylitis, rheumatoid arthritis and Behçet's disease.…”
mentioning
confidence: 99%